Process Mining Techniques in Internal Auditing: A Stepwise Case Study - Santoro, Flavia Maria; Revoredo, Kate Cerqueira; Costa, Rosa M.M.; Barboza, Thais Mester (Histórico da iSys - Brazilian Journal of Information Systems (SERVIDOR ANTIGO - UNIRIO), 2020)
A business process is a sequence of activities organized in a logical way in order to produce a service or a product that is valued for a particular group of customers. Process auditing in corporate environment aims to assess the degree of compliance of processes and their controls. Due to the volume of information that needs to be analyzed in an audit job, auditing´s cost can be very high. We argue that process mining techniques have the potential to improve this activity, allowing the auditor to meet the short deadlines, as well as bringing greater value to the senior management and reliability in the service provided by the audit. The goal of this paper is to discuss, through a case study, how process mining techniques can optimize and bring agility to the verification of process model compliance against the process actually performed. With this approach, it will be possible to detect errors and/or failures in activities or controls of a running process. The main contribution of this paper is to describe a simple set of steps that could be applied by auditors and experts in order to get introduced and to obtain the first insights in the process mining area.